Cancer stem cell populations are resistant to 5-aminolevulinic acid-photodynamic therapy (5-ALA-PDT) - Chantel P. J. Rice; Vipin Shankar Chelakkot; Noah T. Conohan; Kensuke Hirasawa (Scientific Reports)
Abstract Photodynamic therapy (PDT) is a minimally invasive treatment approved for many types of cancers. PDT involves the administration of photoactive substances called photosensitizers (PS) that selectively accumulate in cancer cells and are subsequently excited/activated by irradiation with light at wavelengths of optimal absorbance. Activated PS leads to the generation of singlet oxygen and other reactive oxygen species (ROS), promoting cancer cell death. 5-aminolevulinic acid (5-ALA) is a naturally occurring PS precursor, which is metabolically converted to the PS, protoporphyrin IX (PPIX). Although 5-ALA-PDT is effective at killing cancer cells, in prior studies conducted by our group we normally observed in in vitro experiments that approximately 5–10% of cells survive 5-ALA-PDT, which served as an impetus for further investigation. Identifying the mechanisms of resistance to 5-ALA-PDT-mediated cell death is important to prevent tumor recurrence following 5-ALA-PDT. Previously, we reported that oncogenic activation of Ras/MEK promotes PPIX efflux and reduces cellular sensitivity to 5-ALA-PDT through increased expression of ABCB1 transporter. As cancer stem cells (CSCs) are known to drive resistance to other cancer treatments and have high efflux of chemotherapeutic agents via ABC-family transporters, we hypothesize that CSCs underlie 5-ALA-PDT resistance. In this study, we determined (1) if CSCs are resistant to 5-ALA-PDT and (2) if CSCs play roles in establishing resistant populations of 5-ALA-PDT. When we compared CSC populations before and after 5-ALA-PDT, we found that CSCs were less susceptible to 5-ALA-PDT. Moreover, we found that the CSC population was enriched in 5-ALA-PDT-resistant cell lines compared to the parental cell line. Our results indicate that CSCs are not sensitive to 5-ALA-PDT, which may contribute to establishment of 5-ALA-PDT resistance.